Ballad for Sophie - Melo, Filipe; Melo, Filipe (Top Shelf Productions, 2021)
"When a young journalist prompts a reclusive musical superstar to finally break his silence, he pours out an astonishing saga of rivalry and regret, starring child prodigies and bitter old men, beautiful dancers and demonic managers, Nazi commandants, compassionate nuns, and lifesaving animals. Ballad for Sophie is a sweeping tale that spans the twentieth century, packed with all the drama of a rock & roll biopic and more twists than a night at the opera."